MASALAH DAN SOLUSI MAHASISWA FAKULTAS KEDOKTERAN TAHAP PROFESI UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA PEMBELAJARAN DALAM JARINGAN (DARING) PADA MASA PANDEMI - SAUMA, YUSNITA NUR; SIREGAR, SITI MASLIANA (JURNAL ILMIAH MAKSITEK, 2024)
Since the Covid-19 pandemic, there has been a change in the teaching and learning process, so that the world of medical education is faced with new challenges where learning is usually done face-to-face, turning into non-face-to-face learning. In particular, in the Medical Professional Education Study Program (P3D), students cannot meet directly with patients due to the pandemic and this has hampered the learning process and medical professional development. Objective To find out the problems and solutions of online learning for P3D students. This type of research is descriptive with a cross-sectional design. Data retrieval using the total sampling method as many as 81 respondents were taken from P3D students batch 2019 by distributing questionnaires online with google forms, then filled out and collected. Furthermore, the data is processed using SPSS. Results the most problems were found in history taking with statements of not being able to take anamnesis as many as 48 respondents (59.26%), physical examination problems with statements not being able to do a physical examination directly as many as 50 respondents (61.73%), diagnosis problems and others. Another question with questions during the online learning process did not get a hospital or clinical situation as many as 27 respondents (33.33%) Conclusion the majority of P3D students chose the most problems on physical examination problems and were given a solution to make a physical examination simulation video by considering the risks and benefits